Convection in Ferromagnetic Nanoliquids Under Terrestrial Gravity Condition With the Effect of Non-Inertial Acceleration - Rajashree, S.; Chandrashekara, N. P. (Communications in Mathematics and Applications, 2023)
The stability analysis of Rayleigh-Bénard convection subject to the effect of non-inertial acceleration is performed in the presence of nano-sized ferromagnetic particles-Fe\(_3\)O\(_4\), with water, engine oil and kerosene as base fluids subject to external uniform magnetic field. The plots for thermal Rayleigh number and magnetic Rayleigh number versus wave number for different values of Lewis number (Le) and Taylor's number (Ta) are plotted and discussed in detail. Velocity profiles with the effect of non-inertial acceleration of ferrofluid has also been obtained in the study.
Keywords: Newtonian ferrofluid; Non-inertial acceleration; Fe3O4-magnetite nanoparticles; Rayleigh-Bénard convection